Third sector socio-economic models: how awaqf fits in? - Mohd Arshad, Mohd Nahar; Haneef, Mohamed Aslam; Mat Ghani, Gairuzazmi; Mohamed, Mustafa Omar (2014)
In this paper, we investigate various theoretical frameworks of third sector (voluntary sector) economy with an aim to propose for a sustainable and inclusive socio-economic development model. An economic model that incorporates the third sector, together with the public and private sectors, is argued to be not only economically viable, but ethically superior, in achieving socio-economic development. Waqf is considered to be one of the most important institutions of third sector that exists in the Islamic heritage. Waqf, like many other third sector organisations (TSOs), needs to be recognized formally in efforts at building contemporary economic development frameworks. To achieve this, the paper calls also for multi-dimensional improvements in the management of TSOs, including waqf